Preliminary Study of SurfactinProduction by Malaysian Local Isolates of Bacillus Subtilis - Hasan, Saed Abdullah; Hamad, Ahmed M A; Mohammad, Hana S.; Abdulrazeg, Amena. A. (Al-Mukhtar Journal of Sciences, 2023)
Surfactin is one of the most powerful lipopeptidebiosurfactants produced by various strains of Bacillus subtilis. It has exceptional surface activity, with antiviral, antibacterial, and antitumor properties. The four local isolates, which were named Bacillus subtilis1M, 3M, 7M, and 8M were provided by the School of Biosciences and Biotechnology, Faculty of Science and Technology, University of Kebangsaan, Malaysia. In this study, fermentation on shaker flasks was carried out to assess the ability of four local isolates of Bacillus subtilis strains to produce surfactin by using Cooper’s media formulation, and comparing their production with a commercial strain of Bacillus subtilis ATCC 21332, which was obtained from the American Type Culture Collection. High-Performance Liquid Chromatography (HPLC) was used for surfactin identification and surfactin concentration measurements. Results obtained show the four local isolates have the ability to produce surfactin. The Bacillus subtilis3M strain showed the highest amount of surfactin production with 117 (3) mg/L, while the Bacillus subtilis1M strain produced the lowest amount with 65 (5.4) mg/L. In addition, the production of Bacillus subtilis ATCC 21332 strain was found at 101(4) mg/L under the same fermentation conditions.